2018
DOI: 10.1016/j.combustflame.2018.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Large eddy simulation of pressure and dilution-jet effects on soot formation in a model aircraft swirl combustor

Abstract: Large eddy simulation of pressure and dilution-jet effects on soot formation in a model aircraft swirl combustor, Combust. Flame 192 (2018) 452-472

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 52 publications
3
37
0
Order By: Relevance
“…While there has been considerable progress in the modeling of soot formation processes [8,9] , the application of these advances to realistic combustor configurations still remain sparse. Previous studies [10][11][12][13][14] have shown that while the overall features of the flow can be captured rather accurately, prediction of soot volume fraction is highly sensitive to a host of conditions including small errors in flow field predictions and the choice of soot evolution models.…”
Section: Article In Pressmentioning
confidence: 99%
See 4 more Smart Citations
“…While there has been considerable progress in the modeling of soot formation processes [8,9] , the application of these advances to realistic combustor configurations still remain sparse. Previous studies [10][11][12][13][14] have shown that while the overall features of the flow can be captured rather accurately, prediction of soot volume fraction is highly sensitive to a host of conditions including small errors in flow field predictions and the choice of soot evolution models.…”
Section: Article In Pressmentioning
confidence: 99%
“…The study is based on the DLR ethylene/air combustor [32] , which is comparable in design to a richquench-lean (RQL) type combustor used for aircraft propulsion. This combustor has also been studied using specific methods in the past [10][11][12][13] , which will provide additional bases for comparison. Here, three different soot inception models and three different soot description approaches are compared with experimental data.…”
Section: Article In Pressmentioning
confidence: 99%
See 3 more Smart Citations